Church Music Ministry In Worship According To Pierre Bourdieu's Social Practice Theory Approach - Agus Budi Handoko; Sunarto Sunarto; Suharto Suharto; Agus Cahyono (Universitas Negeri Semarang, 2023)
Music has an influence on human life, including in religion. The Church exists and stands as part of a social group in society, which means that it is also related to social conditions that can be examined from a sociological approach and perspective. This article seeks to describe and explain the three elements of Pierre Bourdieu's social construction (i.e., field, habitus, and capital), which will then be linked to social practices in the Church music ministry at GKI Gejayan. The main activity of the Church is worship, where there is a congregation that is the focus of service (that is served), worship leaders, and a place of worship that all require good arrangement and management. Church music is included in worship. The music ministry in the Church needs to be maximized so that worship can be more attractive, encouraging and motivating the congregation to come together and worship.